An annotated checklist of the main representatives of meiobenthos from inland water bodies of Central and Southern Vietnam. I. Roundworms (Nematoda) - Gusakov, Vladimir A.; Gagarin, Vladimir G. (Zootaxa, 2017)
This paper presents an annotated list of nematode taxa found in the course of investigations of meiobenthic communities in various freshwater bodies in central and southern Vietnam. Data on the structure and abundance of populations, ecology, and global and local distribution are given along with taxonomic and other comments. The occurrence and level of taxonomic richness of roundworms in the studied bodies of water and biotopes are discussed briefly. In total, 127 taxa of 10 orders and 38 families of nematodes are listed. The number of recorded genera is 60; 72 representatives of these genera are identified to species level. The listing includes 48 taxa that had not been previously recorded from Vietnamese territory and 17 species originally collected, analyzed, and described as new to science from this country. The results of these investigations and an overview of the previously published data indicate that taxonomic composition and diversity of Nematoda in Vietnamese freshwater habitats remain poorly studied, except for certain areas.